2011
DOI: 10.2748/tmj/1325886288
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-free actions of finite groups on the Cuntz algebra $\mathcal{O}_\infty$

Abstract: We show that any faithful quasi-free actions of a finite group on the Cuntz algebra O ∞ are mutually conjugate, and that they are asymptotically representable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The reader is referred to [36] and [39] for the classification of Kirchberg algebras, and to Introduction of the first part [22] for a brief account of the classification of group actions on classifiable C * -algebras. Here we just give an incomplete list [1], [14], [17], [18], [20], [24], [25], [26], [27], [28], [30], [31], [34], [35] of classification results on discrete amenable group actions on classifiable C * -algebras.…”
Section: Introductionmentioning
confidence: 99%
“…The reader is referred to [36] and [39] for the classification of Kirchberg algebras, and to Introduction of the first part [22] for a brief account of the classification of group actions on classifiable C * -algebras. Here we just give an incomplete list [1], [14], [17], [18], [20], [24], [25], [26], [27], [28], [30], [31], [34], [35] of classification results on discrete amenable group actions on classifiable C * -algebras.…”
Section: Introductionmentioning
confidence: 99%
“…This technique will lead us to prove a special cohomology vanishing result for specific kinds of cocycles, which will form a useful technical tool for our purposes. As an application of this technical tool, we prove an existence result for G-equivariant * -homomorphisms from certain model actions into certain saturated G-C * -dynamical systems, in part drawing inspiration from [20]. This approach is in line with the philosophy that the concept of saturation (in its various forms), just like ultrapowers, allows one to carry over certain techniques to solve approximation problems that would otherwise be inaccessible outside of a finitary situation.…”
Section: Introductionmentioning
confidence: 84%
“…It is even unclear whether it is redundant if one assumes that α is KK G -equivalent to the trivial Gaction on D. This latter condition is known to hold if α is a quasi-free action on O ∞ ; see [65,Section 4]. Indeed, the main result of [20] shows that for finite groups, any faithful and quasi-free action on O ∞ is conjugate to the model action in Example 3.6. However, the proof uses certain techniquess that are not readily available for infinite groups.…”
Section: Remark 412mentioning
confidence: 99%
“…Note that Izumi also showed that there exist uncountably many mutually non-conjugate outer actions of Z 2 on O 2 . Also, Goldstein and Izumi obtained an equivariant Kirchberg-Phillips type result for finite group actions on O ∞ in [17].…”
Section: Introductionmentioning
confidence: 99%